Comparing original and universal screwdrivers in terms of torque loss in the abutment screw - Vasilios Alevizakos; Nadine Achilles; Björn Rahlf; Philipp Jehn; Marcus Schiller (Wolters Kluwer Medknow Publications, 2021)
Objective: The aim of this study was to examine whether tightening or loosening the abutment screw results in torque loss and whether there is a difference in this respect between original screwdrivers and universal screwdrivers. Materials and Methods: For the purpose of the study, two groups were formed, with the original screwdriver used in group 1 and the universal screwdriver used in group 2. One Straumann implant and one BEGO implant were each inserted into a stationary torque transducer. The next step was to screw 13 abutments into each implant with 13 original abutment screws, using the screwdriver assigned to the group with the torque specified by the manufacturer. To establish whether the torque transmitted to the abutment screw via the screwdriver is also transmitted to the implant rather than causing deformation of the screw head or being transmitted to the surrounding area, the actual torque transmitted from the screw to the implant was measured and recorded electronically during the experiment. Results: There was no loss of torque in the transmission of the tightening torque to the Straumann implant with either screwdriver (P > 0.05). There was a loss of torque in the transmission of the tightening torque to the BEGO implant when using the universal screwdriver but not with the original screwdriver (P < 0.01). Relative to the previously applied tightening torque, a loss of torque when loosening the screw was found with both screwdrivers, both Straumann (P > 0.05) and BEGO (P < 0.05). Conclusion: Using universal screwdrivers can result in loss of torque. The loosening torque is thus decreased, which in turn increases the likelihood of complications such as screw loosening.